Serological Evidence and Coexposure of Selected Infections among Livestock Slaughtered at Eastern Cape Abattoirs in South Africa - Mazwi, K. D.; Kolo, F. B.; Jaja, I. F.; Bokaba, R. P.; Ngoshe, Y. B.; Hassim, A.; Neves, L.; van Heerden, H. (International Journal of Microbiology, 2023)
Zoonotic infections were investigated in a cross-sectional study on asymptomatic livestock slaughtered in abattoirs in the Eastern Cape. Antibodies against Brucella spp., Coxiella burnetii, Toxoplasma gondii, and the coexposure were investigated in sera using serological tests. A total of 565 animals comprising of 280 cattle, 200 sheep, and 85 pigs were screened using RBT, iELISA, CFT, and AMOS-PCR. The Mast® Toxoreagent test and iELISA were used for the detection of T. gondii and C. burnetii, respectively. The Brucella positivity based on at least two tests was 4.3% (12/280), 1.0% (2/200), and 0.0% (0/85) in cattle, sheep, and pigs, respectively. Toxoplasma gondii seropositivity of 37.90% (106/280), 1.50% (3/200), and 7.10% (6/85) was observed in cattle, sheep, and pigs, respectively. Coxiella burnetii seropositivity of 26.40% (74/280), 15.00% (30/200), and 2.40% (2/85) was observed in cattle, sheep, and pigs, respectively. Coexposure was detected in cattle for positivity against C. burnetii and T. gondii 40.54%, Brucella spp. and T. gondii 1.35%, and Brucella spp. and C. burnetii 4.05%. Coexposure for Brucella spp., C. burnetii, and T. gondii 4.05% was detected in cattle. Coexposure of Brucella spp. and C. burnetii 6.67% was detected in sheep. The AMOS-PCR identified B. abortus in cattle and a mixed infection of B. abortus and B. melitensis in sheep in 64.71% seropositive samples. To our knowledge, the coexposure of Brucella spp., T. gondii, and C. burnetii in cattle has not been reported. Coexposure of Brucella spp. and C. burnetii in cattle and sheep is significant as it results in reproductive losses and constitutes an infectious risk to humans. The detection of antibodies against multiple zoonotic infections in livestock from abattoirs has implications for public health.